Impact of indoor plants on work engagement and well-being perceptions - Bloch, Lara Gabriella (My University, 2017)
Much evidence exists with regard to indoor plants and their positive effect on psychological perceptions as well as environmental air quality. However, this type of research has only ever been conducted once in a South African setting, which can be argued, is different to international contexts, in terms of climate and financial status. Indoor plants and their positive effects may have monumental effects on employees. This research assessed the presence of plants, on a sample of 34 employees at Discovery VitalityLife, consisting of Human Resources workers and call centre agents, on psychological perceptions (work engagement; psychological well-being; physical well-being and aesthetics) and on environmental factors (Total Volatile Organic Compounds; Benzene; Xylene; Carbon Dioxide (CO2); temperature and relative humidity). This research was conducted over a period of approximately three months whereby at Time 1 plants were absent and Time 2 plants were present. The same questionnaires were administered at both times. So too were Volatile Organic Compounds measured weekly and three measurement devices were installed in the workplace taking measurements of CO2, humidity, and indoor temperature every hour. The results found were that there were no statistically significant differences for the psychological perceptions from Time 1 to Time 2. This was concluded to be a result of the context in which this research took place. Total Volatile Organic Compounds, Benzene and relative humidity levels statistically significantly decreased at Time 2. Xylene levels statistically significantly increased at Time 2. There was no evidence to suggest statistically significant differences for CO2 and temperature from Time 1 to Time 2.
A research project submitted in partial fulfilment of the requirements for the degree of MA by coursework and Research Report in the field of Industrial Psychology in the Faculty of Humanities. University of the Witwatersrand, Johannesburg. February/May 2017
Keywords: House plants in office decoration; Offices--Health aspects; Air--Purification; Industrial hygiene